Emergency contraceptive pill knowledge, attitudes and dispensing practices of pharmacists in Ibadan and Lagos metropolis, Nigeria (2010)
Use of Emergency Contraceptive Pills (ECP) is desirable in Nigeria where there is high rate of unwanted pregnancy. Pharmacists are expected to play important role in promoting use of ECP but few studies have assessed their knowledge, attitude and dispensing practice of this product in Nigeria. A total of 211 randomly selected pharmacists practicing in Ibadan and Lagos metropolis completed a questionnaire that assessed knowledge about ECP, attitude towards this contraceptive and actual dispensing practices. The results showed that the mean age of the respondents was 38.8 (±10.9) years. There were more male (57.3%) than female respondents (42.7%). The overall mean knowledge scores for the sample was 8.9 (SD: 2.6) out of 18. No significant difference was found in mean knowledge score of male (9.0) (± 2.6) and female respondents (8.9) (±2.8) (p>0.05). Respondents who had practiced for up to 30 years had significantly higher score (9.1) than those with less years of experience (7.7) (p< 0.05). Forty-three percent claimed they had religious or moral (46.9%) objection to dispensing ECP. The majority (79.1%) had ever dispensed ECP whereas 21.9% had never done so. Of the 167 respondents who had ever dispensed, 94.6% had a stock of ECP on the day of their interview. More respondents from Ibadan than Lagos had ever dispensed ECP (p<0.05). More community (80%) than hospital based (60%) pharmacists had dispensed ECP (p<0.05). Only 17.5% of those who had ever dispensed ECP had ever received a formal training on the mode of action of this drug. Although majority had dispensed ECP, their knowledge of the drug is limited. There is need for pharmacists to receive continue education on ECP to enable them serve better the clients who need this service.